2018
DOI: 10.12988/ces.2018.8263
|View full text |Cite
|
Sign up to set email alerts
|

Potential for degradation of lignocellulosic biomass via alkaline pretreatment using corn crop residual biomass

Abstract: The increasing interest in the development of renewable energy sources such as biogas or bioethanol has led to study different lignocellulosic biomass as feedstock. In this work, corn biomass (stalk and leaf) was used to obtain total reducing sugar (TRS) and evaluate its suitability as feedstock for biofuels production. Biomass characterization was carried out by high performance liquid chromatography (HPLC) technique in order to determine main components (cellulose, hemicellulose, and lignin). For TRS quantif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…− and PO 4 3− removal was enhanced due to surface modification with Al of biochar synthesized from poplar residues [56]. The bromatological composition of corn stalks has been reported, which presents in their structure cellulose (35-50%), hemicelluloses (20-35%), and lignin (15-20%); the quaternization of the structure could be successful when occurred between hydroxyl groups of these lignocellulosic materials [57]. From the EDS images, C, O, S, and K atoms were observed in higher proportions.…”
Section: Characterization Of the Bioadsorbentsmentioning
confidence: 98%
See 1 more Smart Citation
“…− and PO 4 3− removal was enhanced due to surface modification with Al of biochar synthesized from poplar residues [56]. The bromatological composition of corn stalks has been reported, which presents in their structure cellulose (35-50%), hemicelluloses (20-35%), and lignin (15-20%); the quaternization of the structure could be successful when occurred between hydroxyl groups of these lignocellulosic materials [57]. From the EDS images, C, O, S, and K atoms were observed in higher proportions.…”
Section: Characterization Of the Bioadsorbentsmentioning
confidence: 98%
“…As Donnan's theory illustrates [70], anion charge is an essential feature of the yield in the adsorption mechanism; it may lead to selective phosphate adsorption on both adsorbents evaluated against nitrate. Thus, considering that the adsorption of both anions under study has been reported to occur by Van der Waals forces, ion exchange and surface complex formation are involved due to the heterogeneity of their structure and binding sites [8,57].…”
Section: Adsorption Equilibriummentioning
confidence: 99%